How to disagree better: utilizing advocacy-inquiry techniques to improve communication and spur behavior change - Alyssa Y. Castillo; Jeannie D. Chan; John B. Lynch; Chloe Bryson-Cahn (Cambridge University Press, 2023)
The ability to provide feedback to a colleague is a key skill required for professional growth and patient safety. However, these conversations are limited by time constraints, differences in values, and a culture of "noninterference." This advocacy-inquiry-identify-teach framework creates an organized approach to initiating successful "challenging" conversations with peers.